INFLUENCE OF PHOSPHOROUS AND UREA ON THE MAGNETIC AND MECHANICAL PROPERTIES OF NANOSTRUCTURED FEPTP FILMS - T. M. Selvakumari; P. Muthukumar; S. Ganesan; R. N. Emerson
The properties of hard magnetic FePtP films electrodeposited in the presence of urea as additive and phosphorous acid as a precursor with varying concentrations were studied with respect to thickness of the films. Films were electrodeposited in various current densities in order to get different thickness and uniform deposits. Elemental composition of the films was obtained using energy dispersive X-ray spectroscopy. Vibrating sample magnetometric studies indicate that additives have favourable impact on the magnetic properties of these films. Structural and surface analysis was carried out using X-ray diffractometry and scanning electron microscopy, respectively. Reasons for variation in magnetic properties and structural characteristics are discussed. Hardness and adhesion of the films were also studied.
Keywords: Physics; Electronic structure and electrical properties of surfaces